Leptochilus phanerophlebius (Polypodiaceae), a new species from Fenshuiling National Nature Reserve, southeastern Yunnan, China - Yu, Zhi-Yong; Liang, Zhen-Long; Liang, Zong-Li; He, Hai-Long; Li, Jian-Hong; Zhang, Qin-Wei; Zhang, Liang (Phytotaxa, 2025)
Leptochilus phanerophlebius, a new fern species from Xilongshan in southeastern Yunnan, China, is described as the third new species of Leptochilus discovered in Fenshuiling National Nature Reserve. Morphologically, the new species is intermediate between L. decurrens and L. brevipes, but differs from both by its distinct venation on both surfaces of the sterile lamina. Cytological evidence indicates that the species is a diploid. Phylogenetic analysis based on plastid data resolves it as a sister species to L. hemionitideus.